Sistem Pakar Untuk Mendeteksi Gangguan Pencernaan Pada Manusia - Ranti Vioneka; Dandi Sunardi; Agung Kharisma Hidayah; Harry Witriyono (Jurnal Media Infotama, 2024)
Currently, technology capable of absorbing human thought processes and patterns is known as artificial intelligence. An expert system is a component of artificial intelligence that contains knowledge and experience acquired from an expert in a particular field. The aim of this study is to develop a web-based expert system designed to detect digestive disorders in humans. Its purpose is to provide patients with information about their health status, correlated with their presenting symptoms, with a certain degree of accuracy. Through the use of this expert system, patients have the ability to identify potential digestive disorders based on individual symptoms or combinations of symptoms they may be experiencing. Additionally, it facilitates early detection of digestive disorders without the need to delay treatment until doctors or specialists are available. The method used is Forward Chaining, which involves collecting symptom data to determine the appropriate type of disease. Forward Chaining is a reasoning technique used in expert systems and rule-based systems. It begins with known events or conditions and then attempts to match these events with the IF (combination) clauses from the IF-THEN rules that are available.